Impact of Roads on Environmental Protected Areas: Analysis and Comparison of Metrics for Assessing Habitat Fragmentation - Manuel Sánchez-Fernández; Juan Miguel Barrigón Morillas; David Montes González; José Juan de Sanjosé Blasco (Land, 2022)
The present study focuses on evaluating the effect of fragmentation caused by road infrastructures on a territory with singular characteristics such as low population density and a high proportion of its surface area protected by the Natura 2000 network. Based on the IFI, UFI, <semantics>Meff</semantics> and DIVI metrics, the state of fragmentation of the landscape units (LU) was studied from two different approaches, considering two different protection figures, and the degree of suitability of the metrics used for the objective pursued was analysed. The results show that the expressions proposed for the indicators which measure the fragmentation of landscape units (LU) originated by road infrastructures (IFI, <semantics>Meff</semantics> and DIVI) assess different causes and consequences in the territory than that proposed for fragmentation originated by urban areas (UFI). The combination of all indicators allows for the identification of shortcomings and strengths of the LU analysed and, consequently, evaluation of the effectiveness of the design of the LU and need for improvement. The outcomes of fragmentation analysis of the LU in the area under study varied depending on the criterion applied and the protection figure considered. A general increasing trend for all indicators was found in terms of the number of LU units and LU surface as the level of fragmentation rises. The results of this study are useful for decision-making on territory and road infrastructures management and new approaches to the organisation of the Natura 2000 network.